Design of a Boarding House Management Information System with Administration and Financial Report Features - Abdul Khaliq; Fachrid Wadly; Banyu Yusadewo (Journal of Information Technology, computer science and Electrical Engineering, 2025)
The rapid growth of boarding house businesses requires effective and accurate information management to support daily administrative and financial activities. Manual data processing in boarding house management often leads to inefficiencies, data redundancy, and errors in financial reporting. This study aims to design a Boarding House Management Information System with administration and financial report features to improve operational efficiency, data accuracy, and financial transparency. The system is designed using a web-based approach that supports the management of tenant data, room data, rental contracts, payment records, and automated financial reporting. The system development process follows the System Development Life Cycle (SDLC) methodology, including requirement analysis, system design, implementation, and testing stages. Unified Modeling Language (UML) diagrams are used to model system processes and database structures. The results of this study produce a management information system that facilitates administrative tasks such as tenant registration, room management, and payment monitoring, as well as financial report generation including income and expense reports. The implementation of the system is expected to reduce administrative errors, enhance data accessibility, and support decision-making for boarding house owners and administrators.